Epidemiological investigations of human rabies in China - Song, Miao (BioMed Central, 2009)
BACKGROUND: The epidemic of rabies showed a rising trend in China in recent years. To identify the potential factors involved in the emergence, we investigated and analyzed the status and characteristics of human rabies between 1996 and 2008. Moreover, the status of rabies infection and vaccination in dogs, and prophylaxis of humans after rabies exposure were analyzed. METHODS: Human rabies data in China between 1996 and 2008 collected from the annual reports of Chinese Center for Disease Control and Prevention (China CDC) were analyzed. To investigate the status of dogs and postexposure prophylaxis (PEP) of humans, brain specimens of domestic dogs were collected and detected, and the demographic details, exposure status and PEP of rabies patients were obtained in 2005 and 2006 in Guangxi, Hunan and Guizhou provinces. RESULTS: The results showed 19,806 human rabies cases were reported in China from 1996 to 2008, with an average of 1,524 cases each year, and the incidence almost was rising rapidly, with the peak in 2007 (3,300 cases). It was notable that nearly 50% of the total rabies cases nationwide were reported in Guangxi, Hunan and Guizhou provinces. In these three provinces, the rabies infection rate in dogs was 2.3%, and 60% investigated cities had a dog vaccination rate of below 70%; among the 315 recorded human cases, 66.3% did not receive any PEP at all, 27.6% received inadequate PEP, and only 6.0% received a full regime of PEP. CONCLUSIONS: In recent years, rabies is reemerging and becoming a major public-health problem in China. Our analysis showed that unsuccessful control of dog rabies and inadequate PEP of patients were the main factors leading to the high incidence of human rabies in China, then there are following suggestions: (1) Strict control of free-ranging dogs and mandatory rabies vaccination should be enforced. (2)Establishing national animal rabies surveillance network is imperative. (3) PEP should be decided to initiate or withhold according to postmortem diagnosis of the biting animal. (4) The cost of PEP should be decreased or free, especially in rural areas. (5)Education of the public and health care staff should be enhanced.